On some Late Helladic migrants into Anatolia named in Hittite and Luwian sources, their migration to Iron Age Cilicia and their return to Greece in legend - Durnford, Stephen P. B. (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
I offer the novel and speculative propositions that 15th-14th century Hittite records of intrusion by Attarissiya of Ahhiya refer to the legendary migration from Thebes into ‘Caria’ by one of several men named Tiresias, presumably via Chios, and that teiresías is an aphaeretic form of attarissiyas, and khíos of aḫḫiyā. Further, presuming that Anatolians had initially encountered Mycenaeans as coming from Chios, I suggest that aḫḫiyawā, ethnicon of aḫḫiyā and the Anatolian exonym for Mycenaeans, was used for Greek *akhaiwíya by folk-etymology. The recurring Linear B names *etewokléwes, *wroikos and *mokʷsos occur in Anatolian sources altered by Luwic pronunciation, showing that Ahhiyawa and Hattusa communicated orally via bilingual speakers working with scribes. Led by *mokʷsos, Tiresias’s linguistically mixed descendants, whose deeds were later imported into Greek as non-Homeric narratives, took the coastal route to Cilicia under their aphaeretic endonym ḫiyawa. They settled in Pamphylia (Hittite ‘Lukka’) by the 13th century, then spread, after Hittite power vanished, into Cilicia Pedias by the 10th century (Herodotus’s Hypachaioi) and founded the kingdom of Hiyawa, whose royal names descend from *wroikos and *mokʷsos. The relevant attestations, linguistic processes and chronology offer a consistent pattern, with traces in Iron Age Lydia and Phrygia too.